Reading Interest through Think Pair Share and Team Games Tournament: Minat Baca melalui Think Pair Share dan Team Games Tournament - Imamah, Waode Andi Nurul; Munirah; Ratnawati (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Literacy skills are crucial for primary education as they support student comprehension across subjects. Specific Background: However, the reading ability of Indonesian students remains below international averages, highlighting the need for effective instructional strategies. Knowledge Gap: Prior studies often focus on a single cooperative model without comparing their influence on reading motivation. Aims: This study compares the Think Pair Share (TPS) and Team Games Tournament (TGT) models in fostering reading interest among grade V students in Makassar. Results: Using a quasi-experimental design with 70 students, results showed a significant increase in reading interest in both groups, with TPS achieving a higher mean post-test score (82.57) than TGT (72.29). Novelty: The research simultaneously examines two cooperative learning models, emphasizing reading interest rather than only cognitive outcomes. Implications: TPS is recommended for deep comprehension and sustained reading motivation, while TGT is more suitable for creating a competitive and engaging classroom climate. Teachers may combine both approaches to balance comprehension and motivation. Highlight TPS produces higher reading interest gains than TGT. TGT is effective for engagement through competition. Combining TPS and TGT optimizes motivation and comprehension. Keyword Cooperative Learning, Think Pair Share, Team Games Tournament, Reading Interest, Elementary Education